Risk Evaluation of the Use of Derivative Products in Financial Management Strategies - Nianty, Dara Ayu (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study evaluates the risks associated with using derivative products in financial management strategies and their potential impacts on corporate financial stability. By addressing dimensions such as regulatory environments, managerial decision-making, and market dynamics, the study provides a holistic understanding of derivatives' dual role as risk mitigation tools and potential sources of financial instability. Research Design and Methodology: The study employs a qualitative approach using the Systematic Literature Review (SLR) method to synthesize findings from existing research. This method enables the integration of theoretical and practical insights from multiple industries and markets, ensuring a comprehensive analysis of derivatives' impacts. Findings and Discussion: The findings reveal that when used strategically, derivatives enhance cash flow stability, mitigate market risks, and support operational resilience. However, misuse due to high leverage, speculative trading, or inadequate oversight can amplify financial instability. The study underscores the importance of robust regulatory frameworks, corporate governance, and managerial expertise in optimizing derivative strategies. Sector-specific and market-dependent nuances further highlight the need for tailored approaches in managing derivative-related risks. Implications: This research offers practical and managerial insights by advocating best practices such as transparent reporting, independent risk committees, and robust risk management frameworks. Policymakers are encouraged to develop adaptive regulatory measures to mitigate systemic risks. Additionally, the findings highlight the need for organizations to align derivative strategies with long-term financial goals while fostering collaboration between regulators, managers, and stakeholders to enhance economic stability.